SNP identification and validation on genomic DNA for studying genetic diversity in Thunnus albacares and Scomberomorus brasiliensis by combining RADseq and long read high throughput sequencing - Siccha-Ramirez, Zoila Raquel [UNESP]; Maroso, Francesco; Pardo, Belén G.; Fernández, Carlos; Martínez, Paulino; Oliveira, Claudio [UNESP] (Elsevier, 2018)
A combination of a RADseq method (ddRAD) with long read high throughput sequencing (Roche 454) was tuned up in order to identify and validate a set of SNPs useful for gene diversity analysis in two important South American commercial tuna (Thunnus albacares and Scomberomorus brasiliensis). A total of 11 and 21 individuals of T. albacares and S. brasiliensis, respectively, were used for SNP identification. DNA was individually digested with two restriction enzymes (SbfI and SphI) and fragments between 300 and 600 bp selected. Combinatorial barcoding was used to identify individuals by including short sequences (5–7 bp) in the adaptors of each restriction site (P1 and P2). After adaptor ligation, samples were pooled and size-selected, amplified by PCR, and sequenced on a 454 GS-Junior sequencer. A total of 180,779 reads were produced with an average length and coverage of 287 bp and 26x, respectively. Sets of 60 and 79 SNPs were in silico selected for T. albacares and S. brasiliensis, respectively, and were tested and validated in 74 and 66 individuals, respectively, on a MassARRAY platform. A total of 36 and 47 SNPs were polymorphic and useful for population analysis. A preliminary study on two distant Brazilian populations of both species (∼3000 km) with these SNPs suggested the absence of significant structure among local populations of both species. Our results demonstrate the possibility of combining ddRAD with long read high throughput sequencing for marker development in species with scarce genomic resources.
Keywords: ddRAD; Genetic structure; Long-read high throughput sequencing; Scomberomorus brasiliensis; Thunnus albacares